2021
DOI: 10.3390/md19030175
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Brown Seaweed and/or Nucleotides Improved Shrimp Performance, Health Status and Cold-Tolerant Gene Expression of Juvenile Whiteleg Shrimp during the Winter Season

Abstract: This study was aimed to evaluate the efficiency of Sargassumpolycystum and nucleotides- supplemented diets to improve immune response and cold-tolerance of juvenile Litopenaeus vannamei. Four treatments were evaluated: T1, the control, shrimp received only a basal diet; T2, a basal diet with 500 ppm nucleotides; T3, a basal diet with 500 ppm S.polycystum powdered; T4, a basal diet with 500 ppm nucleotides and 500 ppm S.polycystum powdered. Shrimp were fed experimental diets for 56 days. Results revealed shrimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 75 publications
0
6
0
1
Order By: Relevance
“…Up to date, three publications have reported the survival and fertility of A. guttata. On the one side, Garza-León et al (2017) and Osorio-Treviño et al (2019) carried out partial life table analysis with similar algal densities (N. oculata at 2×10 6 cells/mL) and temperature (25°C) than the present study; an on the other side, Cortez-Silva et al (2022) studied the life cycle but used R. subcapitata as food source and temperature within the interval here tested. In these studies, neither of them employed any substrate in the culture media, and despite A. guttata survived and produced offspring in those conditions, we found out that the inclusion of substrate improved the performance of these chydorids, increasing their rate of population growth and survival.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Up to date, three publications have reported the survival and fertility of A. guttata. On the one side, Garza-León et al (2017) and Osorio-Treviño et al (2019) carried out partial life table analysis with similar algal densities (N. oculata at 2×10 6 cells/mL) and temperature (25°C) than the present study; an on the other side, Cortez-Silva et al (2022) studied the life cycle but used R. subcapitata as food source and temperature within the interval here tested. In these studies, neither of them employed any substrate in the culture media, and despite A. guttata survived and produced offspring in those conditions, we found out that the inclusion of substrate improved the performance of these chydorids, increasing their rate of population growth and survival.…”
Section: Discussionmentioning
confidence: 77%
“…The maximum survival of A. guttata was comprised within values reported for other chydorids (Table 2). The longest survival within the family Chydoridae were reported for organisms grown at 5°C, reaching values of about 100 d. In the subfamily Aloninae survival has registered values of up to 90 d. For instance, Cortez-Silva et al (2022) reported that longevity of A. guttata reached 37 d as maximum (30.9 d average) when chydorids were fed on R. subcapitata, but we found that this species can survive longer when feeding on either C. vulgaris or N. oculata. It is worth pointing out that food source and temperature influenced longevity of organisms and several publications reported no more than one food source or temperature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The upregulation of the penaeidin -3 gene in response to immunostimulant takes up the tank of energy and transcriptional machinery in hemocytes (Wang et al, 2008).In which the upregulation of this gene might cause resource competition with other genes in expression and result in slowing down and stopping the transcription of the other genes that appears the downregulation of the gene. Abdel et al (2021) recorded an upregulated relative expression of panaeidin -4 in all treatments that were supplemented with Sargassum polycystum and nucleotides fed to L.vannamei. A study by Trejo-Flores et al (2018) reported that mRNA expression of the Panaeidin 4 gene was significantly upregulated at 6hr and 12 hr after P.vannamei was fed Aloe vera.…”
Section: Discussionmentioning
confidence: 91%
“…It is known that MyP contains a proprietary blend of plant and algae extracts said to support liver function (Biomin, 2021b). For instance, Abdel-Rahim et al, (2021) reported that when feeding juvenile Litopenaeus vannamei with 500 mg/kg of Sargassum polycystum algae supplemented feed, the ALP activity showed a higher mean of 8.80 U/L compared to the 6.33 U/L mean registered for control animals (no-algae supplemented feed). The source of algae in MyP is not known (undisclosed for patent protection) but seaweed and macroalgae are a rich source of bioactive compounds (Thanigaivel et al, 2014), and some have hepatoprotective activity (Schleder et al, 2018).…”
Section: Discussionmentioning
confidence: 99%